Timing of testosterone discontinuation and assisted reproductive technology outcomes in transgender patients: a cohort study - Mohammad Albar, M.D; Alex Koziarz, M.D., M.Sc; Eileen McMahon, N.P; Crystal Chan, M.D., M.Sc; Kimberly Liu, M.D., M.S.L (Elsevier, 2023)
Objective: To determine if there is an association between the timing of testosterone discontinuation and assisted reproductive technology (ART) outcomes. Design: Retrospectivse cohort study. Setting: Single academic center. Patient(s): We included consecutive transgender patients seeking fertility preservation between October 2019 and April 2021. Patients who identified as transgender on androgens for >1 month on presentation were included. Intervention(s): None. Main outcome measure(s): A linear regression model was used to evaluate the effect of testosterone discontinuation duration on the number of mature oocytes retrieved. Result(s): Eighteen patients (mean age 27.7 [SD 5.2] years, mean body mass index 27.3 [SD 4.6] kg/m2, mean antimüllerian hormone 27.2 [SD 11.8], median antral follicle count 20 [interquartile range (IQR) 14-32]) were included in the analysis. No patient underwent transition-related surgery (eg, oophorectomy, hysterectomy). None of the patients were previously pregnant. Mean time o,n testosterone was 44 (SD 29.6) months. The median time off testosterone until the start of ovarian stimulation was 7.7 weeks (IQR 4.3-20.7). All patients underwent oocyte cryopreservation except one who had embryo cryopreservation. The median total number of oocytes was 11 (IQR 7-14). The median number of mature oocytes was 7.5 (IQR 5-12) oocytes. The univariate regression model evaluating the duration of time off testosterone before ART demonstrated no significant association with the outcome of mature oocytes (regression coefficient, 0.19; 95% confidence interval, -0.13 to 0.50). Conclusion: In a retrospective analysis of transgender patients recently on testosterone undergoing ART, no association was detected between the timing of testosterone cessation and the number of mature oocytes.